MEMBUAT KREASI MAKANAN BERBAHAN BAKU HASIL PERTANIAN LOKAL ( SINGKONG ) - TRI WIDIASTUTI; MARGARETHA PRABA AULIA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
One of the potentials in Selorejo Hamlet, Kemiri Village, Mojosongo District, Boyolali Regency is the number of cassava or cassava plants. Therefore, the Boyolali University independent Community Service Program is focused on processing food made from local agricultural products in the form of cassava. This program aims to empower the community and to improve the people's economy. The methods of implementing the KKN program include: coordination, collection of materials, making brownies and reporting. The impact of the Community Service Program is: People become more aware of cassava creations that can be processed into food that has high economic value, so that it can be used to increase income.